1990
DOI: 10.1177/019459989010200404
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Radiation‐ and Chemotherapy‐Induced Stomatitis

Abstract: Severe stomatitis is a common problem encountered during either radiation therapy or chemotherapy. Most therapeutic regimens are empirical, with no scientific basis. The purpose of this study is to determine the efficacy of various topical solutions in the treatment of radiation- or chemotherapy-induced stomatitis. Eighteen patients were entered into a prospective double-blinded study to test several topical solutions: (1) viscous lidocaine with 1% cocaine; (2) dyclonine hydrochloride 1.0% (Dyclone); (3) kaoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 3 publications
0
20
0
1
Order By: Relevance
“…Relief of pain due to OM was assessed with one of four agents: dyclonine, lidocaine, cocaine, a combination rinse (kaolin-pectin, diphenhydramine, and saline), and a placebo solution. The results indicated that dyclonine provided the greatest degree of pain relief but was the least palatable of the tested agents [17]. No guideline was possible due to insufficient evidence.…”
Section: Dycloninementioning
confidence: 97%
“…Relief of pain due to OM was assessed with one of four agents: dyclonine, lidocaine, cocaine, a combination rinse (kaolin-pectin, diphenhydramine, and saline), and a placebo solution. The results indicated that dyclonine provided the greatest degree of pain relief but was the least palatable of the tested agents [17]. No guideline was possible due to insufficient evidence.…”
Section: Dycloninementioning
confidence: 97%
“…A double-blind randomized trial comparing the efficacy of viscous lidocaine with 1% cocaine to dyclonine, kaolin-pectin plus diphenhydramine and saline, or placebo favored dyclonine but failed to demonstrate a significant difference among the four solutions, mostly due to the low number of enrolled patients. 99 As the duration of pain control by topical anesthetics is usually short, combinations of local anesthetics and mouthcoating agents are frequently applied. 100,101 In patients with severe oral discomfort, however, the systemic use of analgesics has to be emphasized.…”
Section: Local Anestheticsmentioning
confidence: 99%
“…These modalities include viscous lidocaine, cocaine rinses and spray, dyclonine and capsaicin, the active agent of chilli peppers, which desensitises pain receptors. [76][77][78] These agents provide temporary pain relief.…”
Section: Mouthrinses With Anti-infective and Anesthetic Propertiesmentioning
confidence: 99%